Influence of implant design on blood metal ion concentrations in metal-on-metal total hip replacement patients - Matharu, G; Berryman, F; Brash, L; Pynsent, P; Treacy, R; Dunlop, D (Springer Berlin Heidelberg, 2015)
Purpose: Most factors considered to affect blood metal ions following metal-on-metal hip replacement are based on hip resurfacing patients. The study aims were to determine which factors affect blood metal ion concentrations following metal-on-metal total hip replacement (MoM THR). Methods: All unilateral MoM THR patients at one centre with whole-blood cobalt (Co) and chromium (Cr) concentrations measured up to May 2013 were included. Blood sampling was at a mean of 4.5 years (range 1.1–11.8 years) postoperatively. Results: Of 496 patients (mean age 59.1 years; 52.8 % male), blood metal ions >7 μg/l were observed in 9.7 % (n = 48). Large femoral head sizes (≥38 mm) had significantly higher (p < 0.0001) blood metal ions than smaller sizes (28/36 mm). Corail–Pinnacle implants produced significantly lower blood metal ions compared to other implant designs (p < 0.01 Co and Cr). Univariate linear regression demonstrated the only significant predictors of both blood Co and Cr concentrations were femoral head size (R2 = 8.6 % Co and R2 = 3.3 % Cr, both p < 0.0001) and implant design (R2 = 8.8 %, p = 0.005 Co and R2 = 5.1 %, p = 0.003 Cr). When the three THR implant design groups (Corail–Pinnacle, Synergy, Other) were analysed separately, femoral head size no longer significantly affected blood metal ions in any of the three implant design groups. Conclusions: Implant design was the most important factor affecting blood metal ion concentrations. We recommend the regularity of follow-up be tailored to survival rates of various MoM THR designs rather than according to femoral head size.